A Museum's Culinary Life: Women's Committees and Food at the Art Gallery of Toronto. Issue 2 (2nd July 2016) - Mihalache, Irina D.
Abstract: This article explores the work of the Women's Committee and Junior Women's Committee at the Art Gallery of Toronto (AGT) in the 1960s to increase the visibility of the institution through the use of food. The committees organized numerous culinary events at the gallery, such as Men's Lunches, and off site, such as "The Art of Cooking" classes, in partnership with other important commercial actors in the city, primarily Consumers' Gas Company and Canada Packers. The communication tactics with AGT members, networks of relations with sponsors, and strategies for developing menus, creating recipes, and cooking the food established by the women's committees produced a culinary infrastructure inside the gallery and positioned the AGT as a significant cultural producer in Toronto. A focus on the museum's culinary infrastructure offers new knowledge about the work of museums which demonstrates their continuous concern for relevance and their centrality to larger social and cultural projects. Looking deeply and historically inside museums and engaging with its complex internal structure adds nuance accounts about museums which overlook the diversity of the institution's professional communities.